2015
DOI: 10.1007/s10577-015-9483-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional liaisons between transposable elements and satellite DNAs

Abstract: Transposable elements (TEs) and satellite DNAs (satDNAs) are typically identified as major repetitive DNA components in eukaryotic genomes. TEs are DNA segments able to move throughout a genome while satDNAs are tandemly repeated sequences organized in long arrays. Both classes of repetitive sequences are extremely diverse, and many TEs and satDNAs exist within a genome. Although they differ in structure, genomic organization, mechanisms of spread, and evolutionary dynamics, TEs and satDNAs can share sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 103 publications
5
112
0
3
Order By: Relevance
“…No other satDNA carrying microsatellites was found. Taken together, these results suggest the possibility that some satDNAs in L. migratoria originated from TEs, as in other organisms1718.…”
Section: Resultsmentioning
confidence: 57%
“…No other satDNA carrying microsatellites was found. Taken together, these results suggest the possibility that some satDNAs in L. migratoria originated from TEs, as in other organisms1718.…”
Section: Resultsmentioning
confidence: 57%
“…For example, analysis in five complete plant genomes showed that microsatellites were preferentially located in unique regions of the genomes and exhibited a lack of association with transposon-rich regions 38 . It was hypothesized that microsatellite can be derived from TEs and the opposite evolutionary direction may occur 50, 51 . The direction of transition from TE to microsatellite might depend on transposition rate with an optimal value and the opposite transition is linked to recombination rate 50, 51 .…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that microsatellite can be derived from TEs and the opposite evolutionary direction may occur 50, 51 . The direction of transition from TE to microsatellite might depend on transposition rate with an optimal value and the opposite transition is linked to recombination rate 50, 51 . A chromosome-biased association between microsatellites and TEs in our study is presumably at least partially related to their distant contact and recombination behavior of chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…A body of non‐avian evidence suggests direct involvement of TEs in shaping centromere architecture (reviewed in Refs. and ), and we note that centromeric TEs can thereby affect speciation through the meiotic process of centromere drive (reviewed in Refs. and ).…”
Section: Third‐generation Genome Assemblies and The Future Of Avian Gmentioning
confidence: 96%